2015
DOI: 10.12707/riii13170
|View full text |Cite
|
Sign up to set email alerts
|

Content and violation of the psychological contract among head nurses

Abstract: Enquadramento: O estudo foca-se no conceito do Contrato Psicológico (CP) na perspetiva de que a perceção das obrigações existentes entre empregador e empregado é construída pelo indivíduo. Objetivos: Identificar o conteúdo do CP dos enfermeiros chefe, identificar a (in) existência de perceção de violação deste contrato e as reações à eventual perceção de violação. Metodologia: Estudo exploratório descritivo, de abordagem qualitativa, que recorreu à entrevista semiestruturada numa amostra de dez enfermeiros che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…A significant negative relationship was found between psychological contract breach and job embeddedness; thus, the greater the breach is, the lower the job embeddedness of nurses will be. This result supports the argument that breach is associated with negative outcomes such as turnover intent (Clinton and Guest 2014;Rodwell and Ellershaw 2016), early retirement (Dantas and Ferreira 2015), and lower job satisfaction (McCabe and Sambrook 2013;Trybou et al 2016). No previous research was found on the effect of psychological contract breach on job embeddedness.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…A significant negative relationship was found between psychological contract breach and job embeddedness; thus, the greater the breach is, the lower the job embeddedness of nurses will be. This result supports the argument that breach is associated with negative outcomes such as turnover intent (Clinton and Guest 2014;Rodwell and Ellershaw 2016), early retirement (Dantas and Ferreira 2015), and lower job satisfaction (McCabe and Sambrook 2013;Trybou et al 2016). No previous research was found on the effect of psychological contract breach on job embeddedness.…”
Section: Discussionsupporting
confidence: 79%
“…It is also associated with a negative effect on productivity, job performance (Conway and Briner 2005), job satisfaction (Robinson and Rousseau 1994;Rodwell and Ellershaw 2016;Rodwell and Gulyas 2013), the trust relationship (Robinson andRousseau 1994), andorganisational commitment (Mcabe andSambrook 2013;Robinson and Rousseau 1994;Rodwell and Ellershaw 2016), as well as an increase in absenteeism (Conway and Briner 2005). Previous research further indicated that breach of the psychological contract increases turnover intentions and actual turnover (Clinton and Guest 2014;Rodwell and Ellershaw 2016;Robinson and Rousseau 1994), as well as employees taking early retirement (Dantas and Ferreira 2015).…”
Section: Psychological Contractmentioning
confidence: 98%
See 3 more Smart Citations